2011
DOI: 10.1111/j.1600-0579.2011.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic integrity and plagiarism: perceptions and experience of staff and students in a school of dentistry: A situational analysis of staff and student perspectives

Abstract: Introduction:  This project has investigated student and staff perceptions and experience of plagiarism in a large Australian dental school to develop a response to an external audit report. Methods:  Workshops designed to enhance participants’ understanding of plagiarism and to assist with practical ways to promote academic integrity within the school were provided to all students and staff. Anonymous surveys were used to investigate perceptions and experience of plagiarism and to assess the usefulness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
1
30
2
Order By: Relevance
“…There were also statistically significant differences in plagiarism attitudes observed between first year and third year students. These findings are supported by Ford and Hughes (2012) who also found statistical differences amongst students across different levels of study and study programmes in a school of dentistry. As mentioned earlier, TPB posits that one's intention to engage in a particular behaviour depends on one's attitude to that behaviour (Finchilescu & Cooper 2018).…”
Section: Discussion Of Datasupporting
confidence: 64%
“…There were also statistically significant differences in plagiarism attitudes observed between first year and third year students. These findings are supported by Ford and Hughes (2012) who also found statistical differences amongst students across different levels of study and study programmes in a school of dentistry. As mentioned earlier, TPB posits that one's intention to engage in a particular behaviour depends on one's attitude to that behaviour (Finchilescu & Cooper 2018).…”
Section: Discussion Of Datasupporting
confidence: 64%
“…There was not a single study which compared perception of plagiarism amongst MDS postgraduate students. The results of the present study are contradictory to that conducted by Ford and Hughes [9] where no postgraduate dental students identified plagiarism as an issue and the majority of students and staff supported the mandatory use of Turnitin in all courses with the exception of postgraduate students, many of whom [44%] were still undecided on the value of this practice. According to study conducted by Singh et al On dental professionals most of the dental professionals know about plagiarism and they believe that pressure to publish was a major reason along with several others, which accounts for more and more indulgence in plagiarism [10].…”
Section: Discussioncontrasting
confidence: 56%
“…The workshops used presentations and discussions about academic integrity, plagiarism, institutional policies, and/or avoiding plagiarism as the primary instructional strategies with the aim of providing resources, increase awareness, and reducing the risk of plagiarism. *Ford and Hughes (2012) reported that a brief workshop improved students' understanding of plagiarism; however, no statistical tests were conducted. *Morgan and Hart (2013) did not find differences in self-reported cheating or perceptions of cheating between groups of students who did and did not attend a brief academic integrity workshop.…”
Section: Face-to-face Instructionmentioning
confidence: 99%